COMPARISON OF HALAL PRODUCT ASSURANCE PRINCIPLES ACCORDING TO LAW NO. 33 OF THE YEAR 2014 CONCERNING HALAL PRODUCT GUARANTEE WITH REGULATION OF THE MINISTER OF RELIGION NO. 26 OF THE YEAR 2019 CONCERNING IMPLEMENTATION OF HALAL PRODUCT ASSURANCE - Mega Silvia; Hasan Bisri; Ayi Yunus (Globalwriting Academica Consulting & Publishing, 2022)
This article compares the concepts of halal product guarantees outlined in Law No. 33 of the year 2014 on Halal Product Guarantees and Minister of Religious Affairs Regulation No. 26 of 2019 on the Implementation of Halal Product Guarantees. Halal certification is a need for all consumers, particularly Muslim consumers. State attention must therefore be paid to the assurance of halal-compliant products. This study's research method is a normative legal research method, also known as the astute approach, which examines all laws and regulations pertaining to current legal situations. The enactment of Law No. 33 of the year 2014 Concerning Halal Product Guarantee (UUJPH) and Minister of Religious Affairs Regulation No. 26 of the year 2019 Concerning the Implementation of Halal Product Guarantees provides protection and guarantees to consumers by providing halal certification and legal certainty for all goods produced.